Perbaikan Audio System Dan Pemasangan Power Amplifier Sebagai Sarana Peribadahan Di Musholla Nurul Yaqin Desa Sindang Laut - Sunardi; Wawan Gunawan; Barru Arrosyid; Mukhlisin (CV. Multi Kreasi Media, 2024)
The Nurul Yaqin Prayer Room in Sindang Laut Village is a prayer room that organizes religious activities such as praying, reading the Qur'an and the Ta'lim Assembly and other community activities. This prayer room is located at Kp. Tangkil RT/RW 002/04 Sindang Laut Village, District. Carita, Kab. Pandeglang, Prov. Banten. The people's livelihoods include managing tourist attractions, factory workers, freelance workers transporting sand and gravel, farmers and others. The partner's problem is that they do not understand the concept of an audio system and that standard installations around the room have not been utilized that can be used to support the layout and installation of the audio system. This Community Service (PKM) aims to provide education about the concept and provide installations as an implementation of the ecomasjid (Mushola) concept. The targets of the activity were the Sindang Laut sub-district head, RW 04 administrators, RT 002 administrators, DKM Mushola Nurul Yaqin administrators. PkM methods are surveys, problem identification, counseling, training and evaluation. The PkM material consists of counseling, training and carrying out work to repair audio systems and install power amplifiers with DKM and residents of the Nurul Yaqin Mushola. The results achieved by the implementer were good and correct audio and sound installations in accordance with the National Standardization Agency (BSN), namely the Development and Application of Mandatory SNI for Electrical Equipment. This PKM is an implementation of the Tri Dharma of Higher Education in the form of education, community service and research. The results of research and PKM can enrich course material. This PKM activity is also related to the Main Performance Indicators (IKU), namely IKU 2: Students gain experience outside campus, IKU 3: Lecturers carry out activities outside campus and IKU 5: Lecturers' work results are used by the community. This PKM is also an implementation of the Pamulang University College - Electrical Engineering which can be felt by the local community, where Nurul Yaqin is located in the province of Banten. The output is in the form of a journal or intellectual property rights with the title Audio System Repair and Installation of Power Amplifiers as a Worship Facility in the Nurul Yaqin Prayer Room, Sindang Laut Village.